Comparison of Right-side and Left-side Colon Cancers Following Laparoscopic Radical Lymphadenectomy. Issue 2 (7th February 2021) - Kwak, Han Deok; Ju, Jae Kyun; Lee, Soo Young; Kim, Chang Hyun; Kim, Young Jin; Kim, Hyeong Rok
Abstract: Purpose: The colon originates from the midgut and hindgut, with subsequent differentiation into the right and left colon. The embryology, clinical symptoms, incidence, molecular pathways, and oncologic outcomes differ between right and left colorectal cancers. However, the differences have not been fully accepted. Aim of the Study: This study compared short- and long-term outcomes between right and left colon cancers. Materials and Methods: This study included 966 patients who underwent laparoscopic resection with radical lymph node dissection for stage I, II, and III colon cancers between 2009 and 2014 at a tertiary teaching hospital. We excluded cases with fewer than 12 retrieved lymph nodes, emergency operations, synchronous or multiple cancers, and those located in the transverse colon and rectum. Results : The right colon group included 343 (35.5%) patients and the left colon group 623. Female patients had a high incidence of right colon cancer ( p  < 0.001). Right colon cancer had longer operative times ( p  = 0.012), and more bleeding during the operation ( p  = 0.001). The size of the tumor was larger ( p  < 0.001) and more lymph nodes were harvested ( p  < 0.001) on the right side. Vascular ( p  = 0.006) and lymphatic ( p  = 0.004) invasion was greater in the right colon, but left colon cancer showed greater neural invasion ( p  = 0.008). Cancers on the right side also had a tendency to be poorly differentiated ( p  < 0.001). The groups did not differ in disease-free, overall, and cancer-specific survival rates for stage. Conclusion: Although the oncologic outcomes show no significant differences, colon cancer has characteristic, perioperative, and histopathologic differences according to its embryologic origin.